2016
DOI: 10.3109/03009742.2015.1105290
|View full text |Cite
|
Sign up to set email alerts
|

Methotrexate reduces HbA1c concentration but does not produce chronic accumulation of ZMP in patients with rheumatoid or psoriatic arthritis

Abstract: MTX therapy probably does not produce a chronic increase in erythrocyte ZMP or urinary AICAR concentrations. Collectively, our data do not support the hypothesis that MTX improves glucose homeostasis through chronic accumulation of ZMP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…These effects are not necessarily associated with direct actions on insulin resistance and/or pancreatic β cell function [24,25,27], but rather to a reduction of low-grade inflammation by inhibiting the inflammasome [28]. Methotrexate (MTX) also reduces glycosylated haemoglobin (HbA1c) levels and the risk for diabetes in patients with RA [29], likely independently of insulin sensitivity [30].…”
Section: Introductionmentioning
confidence: 99%
“…These effects are not necessarily associated with direct actions on insulin resistance and/or pancreatic β cell function [24,25,27], but rather to a reduction of low-grade inflammation by inhibiting the inflammasome [28]. Methotrexate (MTX) also reduces glycosylated haemoglobin (HbA1c) levels and the risk for diabetes in patients with RA [29], likely independently of insulin sensitivity [30].…”
Section: Introductionmentioning
confidence: 99%
“…Although it is now well established that insulin resistance (IR) represents the pathophysiological hallmark of MS [ 9 ], the mechanism leading to IR/MS in PsA patients is only partially explained by the abnormal metabolic phenotype [ 10 ] and could be accounted for also by the negative impact of TNF-α and other inflammatory cytokines on insulin signaling [ 11 ] and altered balance in adipocytokines [ 12 ]. The so-called “inflammatory” hypothesis is supported by the evidence that disease-modifying antirheumatic drugs (DMARDs) [ 13 ] and biologic agents [ 14 18 ] have been demonstrated to improve insulin sensitivity in inflammatory arthritis patients.…”
Section: Introductionmentioning
confidence: 99%
“…However, in a large retrospective study of patients with RA or psoriasis, use of a TNFi was associated with a decreased risk for diabetes whereas use of methotrexate was not [ 25 ]. In other studies, significant decreases were not seen in the HOMA-IR index with initiation of MTX [ 23 , 24 , 26 ].…”
Section: Introductionmentioning
confidence: 76%
“…Little is known about the role of MTX in insulin resistance and existing studies have conflicting messages. One study observed decreases in HbA1c in RA and PsA patients without diabetes taking MTX [ 23 ]. In addition, the prevalence of metabolic syndrome in patients with RA was found to be lower among patients using methotrexate, though this data may be confounded by the steatohepatitis leading to discontinuation of methotrexate [ 24 ].…”
Section: Introductionmentioning
confidence: 99%